Implemented and Proven Proprietary Technologies Supporting Weapon Training Systems - Krzysztof BIELAWSKI (Wdrożone i sprawdzone autorskie technologie, wspierające systemy szkoleniowe i treningowe uzbrojenia, 2023)
Zakład Automatyki i Urządzeń Pomiarowych AREX Sp. z o.o. (Gdynia, Poland), part of the WB Group, has many years of experience in the production of weapon training equipment at the highest worldwide level. The article presents the proprietary technologies supporting weapon training systems that provide comprehensive training in weapon operation using the most new generation simulators and training systems so that the use of the delivered equipment is as effective, efficient and safe for the users as possible. Creating a range of comprehensive and complex systems that could compete with the largest global players in the defence industry also means the need to cooperate with recognised partners in Poland. The WB Group continues to introduce technological change within the Polish army and defence industry. Acting in the area of specialised electronics and military IT, the WB Group has helped bring the Polish Armed Forces into the 21st century by setting the applicable standards in key areas for national security. The WB Group is a group of companies in the Polish defence industry and an exporter of technologies and concepts to dozens of countries around the world, including the United States of America. In its activities, it is guided by innovation and the creation of breakthrough technological solutions. The adopted business philosophy of the WB Group is expressed in the range of products, including solutions that are unique on a global scale, and implemented in the most demanding markets. Operation on the global markets has stimulated further development of the WB Group.
Keywords: Systemy szkoleniowe i treningowe uzbrojenia